Between the Projection of Danger, Objectification, and Exploitation. Medical Examination of Polish Civilian Forced Laborers before their Deportation into the German Reich - Hallama, Eva (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2020)
Before crossing the German border, Polish civilian forced laborers who had been recruited for work in Nazi Germany had to undergo medical examination and delousing. The German authorities wanted to ensure that they deported only able-bodied persons to Germany who had been examined for being free from infectious diseases and vermin. In this paper, I explore to what extent the medical examinations may be regarded as strategies for the objectification and dehumanization of the forced laborers. Focus is put on the question of how the Nazi authorities defined “work ability” because the medical assessment was decisive for the choice and selection of foreign manpower. As it turns out, the definition of work ability was essentially determined by factors such as the need for manpower, force, and oppression. Thus, I put the medical assessment of the forced laborers’ work ability into the context of Nazi ideology and economic policy.